Job Satisfaction of Medical Teachers in Bangladesh : Who Are More Satisfied? (Bangladesh Journal of Medical Education, 2014)
Introduction: Job satisfaction is a complex function of a number of variables related to the teachers demographic characters, the work itself, pay, work responsibilities, variety of tasks, promotional opportunities, and relation with co-workers etc. A person may be satisfied with one or more aspects of his/her job but at the same time may be unhappy with other things related to the job. Teachers job satisfaction is associated with teachers effectiveness which ultimately affects students achievements. Job satisfaction has been variously linked with increased performance and negatively with absenteeism and turn over. Methodology: It was a cross sectional type of descriptive study, conducted in 10 medical colleges , of these 5 were non government and 5 were public medical colleges for one year (July 2011 to June 2012) with the aim to determine the medical teachers who were more satisfied with their job . Total respondents were 218 teachers selected by convenience sampling,working in preclinical, para clinical and clinical departments of those medical colleges. Pretested, self-administered, structured , anonymous, using English ,questionnaires with Likert scale was used for data collection . Comparison of satisfaction level between male and female teachers, teachers working in nongovernment and government medical colleges, in central and peripheral medical colleges, senior and junior teachers were done by applying unpaired t test. The level of significance was considered as < 0.05 and confidence interval was 95%. 41% teachers were female, 87% were married and 81% had post graduate degrees. Results : Mean age of the respondents were 42 years and they passed 3 years after last promotion. Regarding theme 1-7 there were no significant difference in satisfaction in male and female teachers but in theme 8 (central administration), p value of two tailed unpaired t test was .009. It means that female teachers were less satisfied than their male counter part regarding central administration .Among the 8 themes, central level teachers were more satisfied (p